Evaluation of the MBKM Educational Internship Program and Flipped Classroom Oriented to the CIPP Model - Kholifaturrohmah, Ramita; Siswandari, Siswandari; Hindrayani, Aniek (Universitas Negeri Semarang, 2024)
Government policies in an effort to transform higher education curriculum in Indonesia are implemented in the form of MBKM. One form of MBKM learning activities carried out by the Economics Education Study Program, Faculty of Economics and Business, Jenderal Soedirman University is the MBKM Educational Internship. This study aimed to evaluate the MBKM Educational Internship program and the flipped classroom learning model oriented towards the CIPP model which consists of content, input, process, and product aspects through a quantitative descriptive approach. The population in this study were all students of the Economics Education Study Program, who took part in the MBKM Educational Internship program for the 2021 / 2022 academic year as many as 33 students. The sampling technique used a saturated sample where all the population was the research sample. Based on the evaluation results of the CIPP model in the MBKM Educational Internship program and the application of the flipped classroom learning model, the results show that both of them have a high value category. It can be concluded that the implementation of the MBKM Educational Internship program and the application of the flipped classroom learning model are going well. Both of them had the highest scores in the product evaluation aspect, namely 90.66% in the MBKM Educational Internship and 84.55% in the application of the flipped classroom learning model. Meanwhile, the lowest score was in the context evaluation aspect, namely 83.52% in the MBKM Educational Internship and 73.77% in the application of the flipped classroom learning model.